Effect of oral administration of mushroom Panaeolus infusion on motoric activity and curiousity of male mice - Andreanus A. Soemardji; IG.N.A. Supradja (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2003)
The motoric activity and the curiosity tests on Swiss Webster male mice orally treated with infusion of mushroom panaeolus were studied. A 10% infusion of mushroom administered orally at the dose of 0.5; 1.0 and 2.0 g/kg of body weight showed to decrease in motoric activity and curiousity, but the decrease was less than that shown by diazepam with the dose 5 mg/kg body weight administered intraperitoneally.Keywords :Mushroom, Panaeolus, motoric activity, curiousity.